An analysis of use statistics of electronic papers in a Korean scholarly information repository - Kim, Jayhoon; Bae, Su-yeong; Hwang, Hyekyong; Ko, Sung-Seok (Information research, 2021)
Introduction. This study aimed to analyse the current use status of Korean scholarly papers accessible in the repository of the Korea Institute of Science and Technology Information in order to assess the economic validity of the maintenance and operation of the repository. Method. This study used the modified historical cost method and performed regression analysis on the use of Korean scholarly papers by year and subject area. Analysis. The development cost of the repository and the use volumes were analysed based on 1,154,549 Korean scholarly papers deposited in the Institute repository. Results. Approximately 86% of the deposited papers were downloaded at least once and on average, a paper was downloaded over twenty-six times. Regression analysis showed that the ratio of use of currently deposited papers is likely to decrease by 7.6% annually, as new ones are added. Conclusions. The need to manage currently deposited papers for at least thirteen years into the future and provide empirical proof that the repository has contributed to Korean researchers conducting research and development in the fields of science and technology. The benefit-cost ratio was above nineteen, confirming the economic validity of the repository.